Mobility issues in hierarchical mobile IP - Hassan Abdalla Hashim, Aisha; Anwar, Farhat; Mohd, Shaffiah; Liyakthalikhan, Hatina Banun (2005)
Mobile IP is a powerful protocol that supports Internet mobility. Micro-mobility approach was introduced because Mobile IP suffers in case of frequent movement, i.e. intra-domain mobility. Micro-mobility protocols aim to handle local movement of Mobile Nodes (MNs) without interaction with the Home Agent (HA) through the Internet. This has the benefit of reducing delay and packet loss during handoff and eliminating registration between MN and possibly distant Home Agents (HA) when MN remain inside their local coverage areas. The Hierarchical Mobile IP (HMIP) protocol handles Mobile IP registration locally using a hierarchy of foreign agents. In HMIP, registration messages are sent by the MNs to update their respective location information. This registration messages will establish tunnels between neighboring foreign agents along the path from the mobile node to a gateway foreign agent (GFA). This will form a network of tunnels where packets addressed to the MN will travel. The aim of this research is to study and evaluate HMIP protocol. The paper presents mobility issues in HMIP. The performance analysis of the protocol is carried out using NS-2 simulator. Some recommendation was suggested to improve mobile communication in HMIP. Key words: Hierarchical, Mobile IP, Micro-mobility, Performance Analysis.